(untitled) (GYMNASIUM, 2011)
This article is offering an overview on the activities conducted by the partners in the Erasmus project titled European Masters in Health Rehabilitation through Physical Exercise. The information provided could be useful to those who are interested (universities, students, managers of organizations that operate in the health sector), regarding the new innovative programs in the area of educational provision for health rehabilitation, based on the local communities support.